Iatrogenic air embolisms during endovascular interventions: impact of origin and number of air bubbles on cerebral infarctions - Schaefer, Tabea; Greive, Svenja; Mencl, Stine; Heiland, Sabine; Kramer, Martin; Möhlenbruch, Markus Alfred; Kleinschnitz, Christoph; Bendszus, Martin; Vollherbst, Dominik (Clinical neuroradiology, 2023)
Purpose: Cerebral infarctions caused by air embolisms (AE) are a feared risk in endovascular procedures; however, the relevance and pathophysiology of these AEs is still largely unclear. The objective of this study was to investigate the impact of the origin (aorta, carotid artery or right atrium) and number of air bubbles on cerebral infarctions in an experimental in vivo model. Methods: In 20 rats 1200 or 2000 highly calibrated micro air bubbles (MAB) with a size of 85µm were injected at the aortic valve (group Ao), into the common carotid artery (group CA) or into the right atrium (group RA) using a microcatheter via a transfemoral access, resembling endovascular interventions in humans. Magnetic resonance imaging (MRI) using a 9.4T system was performed 1h after MAB injection followed by finalization. Results: The number (5.5 vs. 5.5 median) and embolic patterns of infarctions did not significantly differ between groups Ao and CA. The number of infarctions were significantly higher comparing 2000 and 1200 injected MABs (6 vs. 4.5; p< 0.001). The infarctions were significantly larger for group CA (median infarction volume: 0.41mm3 vs. 0.19mm3; p< 0.001). In group RA and in the control group no infarctions were detected. Histopathological analyses showed early signs of ischemic stroke. Conclusion: Iatrogenic AEs originating at the ascending aorta cause a similar number and pattern of cerebral infarctions compared to those with origin at the carotid artery. These findings underline the relevance and potential risk of AE occurring during endovascular interventions at the aortic valve and ascending aorta.
Vorab online veröffentlicht: 04. September 2023
Gesehen am 27.10.2023